Space Utilization in the Kalimati Long Storage Reservoir Area: A Study from Henri Lefebvre's Perspective - Mariasari, Ika Fransisca; Hadiwijoyo, Suryo Sakti; Purnomo, Daru (PERSPEKTIF, 2024)
This research aims to explain the form of space utilization in the Kalimati Long Storage Reservoir Area from Henri Lefebvre's perspective which includes the dimensions of spatial practice, spatial representation, and representational space. This research uses a descriptive qualitative method with the research observation unit being the Kalimati Long Storage Reservoir Area, while the unit of analysis is space production in the Kalimati Long Storage Reservoir Area from Henri Lefebvre's perspective. Data collection was obtained through interviews, observation, and documentation. The data analysis techniques of Miles and Huberman are data reduction, data presentation, and concluding/verification. The research results obtained are (1) the form of space utilization of the Kalimati Long Storage Reservoir is used for exercising, enjoying the view, taking selfies, fishing, hanging out and trading (2) the Kalimati Long Storage Reservoir has become a lively space due to community activities which produce interaction (3) the Kalimati Reservoir Long Storage Kalimati can be considered a symbol that can change dysfunctional areas into organized areas for community activities. Space never exists in itself, but out of necessity and demand. The production and reproduction of space will continue to be dynamic following the community's sense of sociality.